Effect of Growth Regulators, Chitosan, and Silver Nanoparticles on Callus Induction and Stimulating the Myricetin Production in Moringa (Moringa Oleifera Lam.) Tree - Bassam Meftin Ewhayid; Majid Abdulhameed Ibrahim; Eman Mohammed Abdulzahra (Zien Journals, 2022)
The study was carried out in the laboratory of Fadak Company for Tissue Culture in Abi Al-Khassib district, and the Laboratories of the College of Pharmacy, University of Basrah, Iraq. The nodule stem segments were used as explants that were taken from five-year-old Moringa trees. These explants were cultured on an MS medium supplemented with benzyl adenine at different concentrations (1, 2, 3, and 4 mg L-1 ) for callus induction. The 50 mg weight of induced callus was cultured on MS medium supplemented with different concentrations of chitosan (0, 5, and 10 mg L-1 ) and silver nanoparticles (0, 10, 20, and 30 mg L-1 ) for stimulating the myricetin production. The treatment of 4 mg L-1 benzyl adenine showed significant superiority in the percentage of explant response to callus induction compared to the other treatments, which amounted to 66.0%. But the treatment of 1 mg L-1 benzyl adenine was recorded the lowest response of explants to callus induction, which amounted to 13.77%. The results also showed that the treatment of 5 mg L -1 chitosan was significantly superior in the content of callus of the myricetin compound compared to other treatments, which amounted to 79.572 moles L-1 . The treatment of 10 mg L-1 silver nanoparticles, which recorded the callus content of myricetin compound, amounted to 26.387 moles L-1 . The leaves of Moringa trees recorded 4.714 moles L-1 myricetin compound. While the treatment of silver nanoparticles at 30 mg L-1 recorded the lowest callus content of myricetin, which was 0.668 moles L-1 .
Keywords: Bioactive compound; callus; explant; HPLC device